Loss of glyoxalase 1 induces compensatory mechanism to achieve dicarbonyl detoxification in mammalian schwann cells - Morgenstern, Jakob; Fleming, Thomas; Schumacher, Dagmar; Eckstein, Volker; Freichel, Marc; Herzig, Stephan; Nawroth, Peter Paul (The journal of biological chemistry, 2017)
The glyoxalase system is a highly specific enzyme system existing in all mammalian cells that is responsible for the detoxification of dicarbonyl species, primarily methylglyoxal (MG). It has been implicated to play an essential role in preventing the increased formation of advanced glycation end products under certain pathological conditions. We have established the first glyoxalase 1 knock-out model (GLO1−/−) in mammalian Schwann cells using the CRISPR/Cas9 technique to investigate compensatory mechanisms. Neither elevated concentrations of MG nor associated protein modifications were observed in GLO1−/− cells. Alternative detoxification of MG in GLO1−/− is achieved by increased catalytic efficiency of aldose reductase toward hemithioacetal (product of glutathione and MG), which is most likely caused by S-nitrosylation of aldose reductase. The hemithioacetal is mainly converted into lactaldehyde, which is paralleled by a loss of reduced glutathione. Inhibition of aldose reductase in GLO1−/− cells is associated with an increased sensitivity against MG, elevated intracellular MG levels, associated modifications, as well as increased oxidative stress. Our data suggest that aldose reductase can compensate for the loss of GLO1. This might be of clinical importance within the context of neuronal diseases caused by an impaired glyoxalase system and elevated levels of dicarbonyl species, such as MG.
First Published on December 12, 2016
Gesehen am 14.05.2018